Synthesis, Characterization and Use of Schiff Bases as Fluorimetric Analytical Reagents (Part II) - Mohamed N. Ibrahim; Salaheddin A. I. Sharif (E-Journal of Chemistry)
Many Schiff bases were prepared by condensation reaction of certain aromatic amines with aromatic aldehydes derivatives and then the fluorescence properties of these Schiff bases were examined in acidic and basic media. It is shown that these compounds can be used for fluorimetric monitoring of small pH changes.